Characterisation of Jhari cattle—A new cattle germplasm from Telangana - PUNDIR, R K; SINGH, P K; DANGI, P S; DAS, S (The Indian Journal of Animal Sciences, 2021)
In the present study, an attempt has been made to characterize and evaluate Jhari cattle of the state. For characterization of Jhari cattle, surveys were conducted in 17 villages of 4 districts. Physical characteristics and morphometric traits were recorded for 193 animals of different age and sex. Production and reproduction performance and socio-economic parameters were recorded from 73 farmers of different villages. Animals were reared on extensive system of management, i.e. grazing only. Few farmers provided supplement feeds to the bullocks only at home during the working days. Animal houses were open with wooden stick and separated from the owner residence (82%). Jhari cattle were gray or white (90%) in body colour. Body was small, compact and in cylindrical shape. Face was convex and longer as compared to other cattle populations of the state which is the differentiating trait of Jhari cattle. Udder was not developed and mostly bowl shaped. Temperament was docile. Birth weight ranged from 12 to 18 kg in female calves and 14-24 kg in male calves. The average daily milk yield was 1.52 kg and ranged from 1.0 to 3.0 kg. Lactation length varies from 100 to 180 days with an average of 152 days. Calving interval ranged from 340 to 610 days. A pair of bullocks may plough 1 acre of land in 6-8 h. It was observed that Jhari cattle are physically distinct from the other cattle populations of the region like Kamma, Vandharvi and Thurupu. Face is the major character for differentiating with other cattle population, i.e. longer and convex type. The other differentiating characters is horns, longer and thin at the base as compared to Ongole or its grades. Keeping in view its significant contribution in livelihood of the farmers and physical traits Jhari cattle population may be registered as a distinct breed.